The Drosophila melanogaster LEM-domain protein MAN1. - Wagner, N.; Kagermeier, B.; Loserth, S.; Krohne, G. (European Journal of Cell Biology, 2006)
Here we describe the Drosophila melanogaster LEM-domain protein encoded by the annotated gene CG3167 which is the putative ortholog to vertebrate MAN1. MAN1 of Drosophila (dMAN1) and vertebrates have the following properties in common. Firstly, both molecules are integral membrane proteins of the inner nuclear membrane (INM) and share the same structural organization comprising an N-terminally located LEM motif, two transmembrane domains in the middle of the molecule, and a conserved RNA recognition motif in the C-terminal region. Secondly, dMAN1 has similar targeting domains as it has been reported for the human protein. Thirdly, immunoprecipitations with dMAN1-specific antibodies revealed that this Drosophila LEM-domain protein is contained in protein complexes together with lamins Dm0 and C. It has been previously shown that human MAN1 binds to A- and B-type lamins in vitro. During embryogenesis and early larval development LEM-domain proteins dMAN1 and otefin show the same expression pattern and are much more abundant in eggs and the first larval instar than in later larval stages and young pupae whereas the LEM-domain protein Bocksbeutel is uniformly expressed in all developmental stages. dMAN1 is detectable in the nuclear envelope of embryonic cells including the pole cells. In mitotic cells of embryos at metaphase and anaphase, LEM-domain proteins dMAN1, otefin and Bocksbeutel were predominantly localized in the region of the two spindle poles whereas the lamin B receptor and lamin Dm0 were more homogeneously distributed. Downregulation of dMAN1 by RNA interference (RNAi) in Drosophila cultured Kc167 cells has no obvious effect on nuclear architecture, viability of RNAi-treated cells and the intracellular distribution of the LEM-domain proteins Bocksbeutel and otefin. In contrast, the localization of dMAN1, Bocksbeutel and otefin at the INM is supported by lamin Dm0. We conclude that the dMAN1 protein is not a limiting component of the nuclear architecture in Drosophila cultured cells.